Matching Poly(vinylidene fluoride) and β″-Al2O3 for Hybrid Electrolyte Membrane for Advanced Solid-State Sodium Batteries. Issue 8 (30th August 2021) - Liu, Wen; Yan, Tingfang; Wang, Yong; Li, Yong; Luo, Ying; Guo, Rui; Zhou, Luozeng; Yang, Cheng; Pei, Haijuan; Xie, Jingying
Abstract : Poly(vinylidene fluoride)-based composite solid electrolyte was prepared for solid-state sodium batteries with a high ionic conductivity of about 4.55 × 10 −4 S·cm −1 at 25 °C and better compatibility with metal Na. For further illustration, solid-state Na/NaNi1/3 Mn1/3 Fe1/3 O2 and Na/carbon fluorides batteries are fabricated and exhibit satisfactory electrochemical performance at 25 °C.